Pemanfaatan Botol Aqua Sebagai Media Tanam untuk Menerapkan Sikap Peduli Lingkungan - Yani, Fitri; Lova, Stelly Martha; Akbar, Wawan; Alisa, Nora (Universitas Methodist Indonesia, 2024)
This activity aims to provide children with an understanding of utilizing plastic bottles for planting media containers at the Kotta Cinna Site Museum and to implement an attitude of caring for the environment towards elementary school children living around the Kotta Cinna Site Museum. Solutions to overcome partner problems include: (1) Providing skills that can be personally useful and have new, more creative creations for elementary school children. (2) Empowering elementary school children to be more skilled, able to work and produce a product from recycled plastic bottles. The method of implementing the activity is carried out through 4 stages, including: (1) Preparation: environmental observation (initial mapping), discussion of problems, and determination of problem solutions; (2) Implementation: implementing a mentoring program; (3) Monitoring and Evaluation: evaluation of the process and results of the mentoring program; and (4) Follow-up: developing a mentoring program in other aspects and on a wider scale. The results of the community service program that have been implemented are as follows: (1) The average success of student understanding as a whole from the 10 questions asked is 95.02% with the Very Good category. Based on these data, it can be concluded that the level of success of the PKM program implemented when measured based on the level of understanding of elementary school children is in the very good category, meaning that it can be understood very well by all elementary school children who participate in the activity as a whole, so through this PKM activity, the Utilization of Plastic Bottles as Planting Media Containers to Reduce the Impact of Environmental Pollution is believed to be able to eliminate waste and air pollution at the Situ Kotta Cinna Museum. (2) This PKM activity in the Utilization of Plastic Bottles as Planting Media Containers to Reduce the Impact of Environmental Pollution can change elementary school children to care about the environment so that they become wise in utilizing plastic bottle waste in the environment. Thus, elementary school students have widely actualized actions that are beneficial to themselves and the surrounding environment in their daily lives at the Situ Kotta Cinna Museum.